PROSPECTS FOR SMPLEMENTING A SUSTAINABLE DEVELOPMENT POLICY FOR UKRAINE’S “GREEN” ECONOMY - Prokopenko, Nataliia (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
In today’s socio-economic climate, the environmental dimension of development is becoming one of the key factors in ensuring the stability of economic systems and enhancing the competitiveness of nations. The intensification of global climate issues, the growing anthropogenic impact on the environment, the depletion of natural resources and the need to implement the Sustainable Development Goals are driving an active transition towards the principles of a ‘green’ economy. The experience of European Union countries, which are implementing a comprehensive policy of environmental modernisation aimed at improving resource efficiency, reducing greenhouse gas emissions, developing a circular economy and establishing environmentally oriented models of economic growth, is of particular relevance. The article examines the main directions of strategic development of the ‘green’ economy in EU countries, identifies the key mechanisms of environmental transformation, and substantiates their importance for ensuring sustainable development in the current context.